2021
DOI: 10.3390/ijerph18168598
|View full text |Cite
|
Sign up to set email alerts
|

Association between Osteoporosis and Low Hemoglobin Levels: A Nested Case–Control Study Using a National Health Screening Cohort

Abstract: An association between anemia and an increased risk of osteoporosis has been suggested. The goal of this study was to estimate the association of hemoglobin (Hb) level with osteoporosis. A total of 69,760 osteoporosis patients aged ≥ 40 years old from the Korean National Health Insurance Service Health Screening Cohort were enrolled. From an identical cohort database, 69,760 comparison participants were randomly selected. Hb levels before the onset of osteoporosis were evaluated. The association of Hb level wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Moreover, our study found that higher Hb and Hct levels were protective factors against osteoporosis. This concurs with other studies [ 54 , 55 , 56 ]. In fact, lower levels of Hb and Hct reflect an anemia status, which increases osteoclast activity [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, our study found that higher Hb and Hct levels were protective factors against osteoporosis. This concurs with other studies [ 54 , 55 , 56 ]. In fact, lower levels of Hb and Hct reflect an anemia status, which increases osteoclast activity [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have concluded that there were significant correlations between hemoglobin levels and BMD in aging populations [ 15 17 ], but this finding remains inconsistent. A recent study showed that people with reduced hemoglobin levels had a higher risk of osteoporosis [ 18 ], while another study showed no such relationship between hemoglobin concentration and BMD [ 19 ]. In addition, some studies showed that anemia increased the risk of fractures but the risk differed by gender.…”
Section: Introductionmentioning
confidence: 99%
“…Men’s Hb levels and BMD were found to be positively correlated in a separate cross-sectional study ( 37 ). Correction of low Hb levels may have a preventative role in osteoporosis prevention ( 38 ). However, there are few findings on the effect of Hb decrease on osteoporosis when the group consists of diabetes people.…”
Section: Discussionmentioning
confidence: 99%